Bunionectomy inside-out: Intracortical medial exostectomy during minimally invasive hallux valgus correction - de Santa Helena Ilha, Thales Augusto; Viana Pereira Filho, Miguel; Freitas, Márcio; Ferreira, Gabriel Ferraz (Journal of the Foot & Ankle, 2026)
In this technical report, we describe an intracortical “inside-out” technique for percutaneous medial exostectomy performed as a final step during modern minimally invasive hallux valgus correction. Contemporary third-generation minimally invasive Chevron-Akin (MICA/PECA) and fourth-generation metaphyseal extra-articular transverse constructs (META) provide powerful multiplanar correction with rigid fixation. However, residual medial bony prominence following distal fragment translation may persist and contribute to postoperative medial irritation. Traditional percutaneous exostectomy is commonly performed in an outside-in fashion and may increase the risk of capsular trauma or inadvertent articular injury when performed close to the first metatarsophalangeal (MTP) joint. Our technique uses the same 2.0-2.2 mm Shannon burr employed for the metatarsal osteotomy, introduced intraosseously through a minimal cortical entry. The medial prominence is progressively resected from cancellous bone toward the medial cortex under fluoroscopic and tactile guidance, while maintaining an outward safety vector away from the articular surface. We hypothesize that this approach provides a reproducible method to contour residual medial prominence while preserving medial capsuloligamentous structures.